Pengajaran dan Pembelajaran di Era Digital - Afif, Nur (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2019)
This article will explore how the dynamics of teaching and learning in the Digital Age. This study contributes to the discussion on how education should position itself in changing times, including in facing the digital age. Through library research, researchers found several important aspects of teaching and learning in the digital era, namely learning in the digital era has different characteristics from student learning in the past, the generation in this era are those who have digital native characters. Students at this time are born, grow and grow in direct contact with the digital world, so that the flow of information obtained will be different from previous students. Therefore, the teacher as a partner in learning must be able to design learning activities so that students get more information than the time provided.